The Conditions of Development of The Anti-Genocide Movement in The Usa in The Context of The Prevention of Genocide in Africa - Kościółek, Jakub (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
The United States of America ratified the Anti-genocide Convention only thirtysix years after its initial signature. It was passed to the Senate for the first time by President Harry Truman in 1949. It evoked great controversy as it was perceived as something that might be favorable to communist regimes and possibly be an attack on the basic rights of US citizens. Successive attempts to pass it began much later in 1970 due to the support from Richard Nixon who backed the ratification initiative. The main reason for the reluctance to pass the convention was its record on international jurisdiction on persons responsible for genocide.